The Chronicles of Narnia : The lion, the witch, and the wardrobe - Lewis, C. S. (Clive Staples) 1898-1963.; Hague, Michael (New York : Scholastic., 2006)
Four English school children find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with eternal winter.
S
b
b
Keywords: Fantasy